Analysis On The Effectiveness Of “Unbundling” And “Open Access” In Indonesian Gas Business Sector - Aritonang, Parulian Paidi (Jurnal Hukum & Pembangunan, 2019)
Natural gas is a very important non-renewable natural resource that controls the lives of many people. Therefore, the exploitation and utilization of natural gas must be carried out wisely and for the greatest prosperity of the people. This is mandated in Article 33 Paragraph (3) of the 1945 Constitution of the Republic of Indonesia that "Earth, water and the natural resources contained therein are controlled by country and used for the greatest prosperity of the people". With the promulgation of Law Number 22 the Year 2001 concerning Oil and Gas, there has been restructuring in the implementation of natural gas exploitation through pipelines in Indonesia. The law provides more space for private entities to engage in gas exploitation with the purpose to create healthy competition, transparency, improving national development, efficiency in exploiting natural gas and to develop competitive price so that the end consumer can enjoy the benefits. By its implementing regulations, namely, the Regulation of the Minister of Energy and Mineral Resources Number 19 of 2009, natural gas exploitation through pipelines is carried out through an “unbundling” and “open access” mechanism.